Service Quality and Customer Satisfaction in J&T Express: A SERVQUAL-Based Study - Saleha Adiba; Husna Leila Yusran; Alvina Hasanah Rachmadanty; Nurkis Dianti; Aliyah Bilkis; Ulfah Nurzakiyyah; Danang Islami (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Service quality, as a determinant of customer satisfaction, will be investigated in this research, focusing on J&T Express, with a SERVQUAL perspective. SERVQUAL methodology focuses its analysis on five service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This study was inspired by the increasing rivalry within the express industry, illustrated by the sudden increase in customer complaints that appear on social platforms, implying that there might be a difference between customer expectations and their perceptions of J&T’s service. Quantitative, cross-sectional design was implemented, with a structured questionnaire administered on a five-point Likert scale. Of the collected data from 130 participants, only 127 were valid. Items were found valid, reliable, and were in a normal distribution. Results show that service quality significantly correlates with customer satisfaction, with a positive correlation (r=0.665) with satisfaction explaining only 44.2% of the variation. Of the five service dimensions, reliability was identified as the most effective dimension, with responsiveness, empathy, and accuracy of COD services identified as dimensions that require improvement. In essence, this study’s outcome provides that improvements in responsiveness, employee empathy, as well as consistent operational procedure, would yield improvements within customer satisfaction at J&T Express.